Intravesical hyaluronic acid treatment improves bacterial cystitis and reduces cystitis-induced hypercontractility in rats - YEGEN, BERRAK; AKAKIN, DİLEK; ŞENER, GÖKSEL; ALPAY, HARİKA; YILDIZ, NURDAN; ÖZDEMİR KUMRAL, ZARİFE NİGAR; İLKİ, ZEYNEP ARZU (WILEY, 2015)
ObjectiveTo investigate the effect of intravesical hyaluronic acid on Escherichia coli-induced cystitis and cystitis-induced hypercontractility in rats. MethodsBacterial cystitis was induced in Wistar female rats by intravesical inoculation of E.coli. Isotonic saline was instilled in the control group (n=6). The rats were either non-treated, treated with gentamycin (4mg/kg, 5days) or treated intravesically with hyaluronic acid (0.5mL, 0.5%). On the eighth day, the bladder tissues were excised for histological examination, and the measurements of myeloperoxidase, superoxide dismutase and catalase activities. Contraction/relaxation responses to carbachol, isoprotrenol and papaverine were studied. ResultsTissue myeloperoxidase activity was increased, but superoxide dismutase and catalase activities were decreased in bacterial cystitis, while hyaluronic acid treatment reversed these changes. In the hyaluronic acid-treated group, healing of the uroepithelium was observed, while decreased inflammatory cell infiltration was obvious in gentamycin-treated group. E.coli-induced cystitis in all rats resulted in increased contraction responses to carbachol compared with controls (P<0.01). Treatment with hyaluronic acid, but not gentamycin, significantly (P<0.05) depressed hypercontractility at maximum carbachol concentrations. In all rats with cystitis, papaverine-induced relaxation was increased, whereas isoproterenol-induced relaxation curves were not different between the studied groups. ConclusionGentamycin treatment, despite its ameliorative effect on inflammation, had no impact on the contractile dysfunction of the injured bladder. Intravesical hyaluronic acid, in addition to its supportive role in the healing of the epithelium, seems to lower the increased threshold for contraction and to reduce oxidative stress. These findings support a potential role for hyaluronic acid in the treatment of bacterial cystitis.
Keywords: cystitis; detrusor hypercontractility; hyaluronic acid; inflammation; rats; URINARY-TRACT-INFECTIONS; OXIDATIVE STRESS; INTERSTITIAL CYSTITIS; BLADDER; PREVENTION; INHIBITION; SULFATE; KIDNEY; INJURY